2019
DOI: 10.1002/chem.201900269
|View full text |Cite
|
Sign up to set email alerts
|

Fully Collapsed Imploded Cryptophanes in Solution and in the Solid State

Abstract: Cryptophanes with flexible linkers derived from (±)‐tris‐(4‐formyl‐phenyl)‐cyclotriguaiacylene with either bisoxydi(ethylamine) or bis(aminopropyl)ether were isolated as single crystals, the crystal structures of which showed the proposed, but previously uncharacterised, out‐in conformation, in which both cyclotriguaiacylene fragments adopt a crown conformation with one crown sitting inside the other. The usual cage‐like out‐out conformation of the cryptophanes was observed when crystals were dissolved upon he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 36 publications
(33 reference statements)
2
12
0
Order By: Relevance
“…The crystal structure revealed that the out‐out CC conformation is crystalized with guests inside the cavity (Figure 2). It is in agreement with the fact that solvent filled cryptophanes are more stable in out‐out CC conformation [14,21] . Four acetone molecules are present in the unit cell.…”
Section: Methodssupporting
confidence: 87%
See 4 more Smart Citations
“…The crystal structure revealed that the out‐out CC conformation is crystalized with guests inside the cavity (Figure 2). It is in agreement with the fact that solvent filled cryptophanes are more stable in out‐out CC conformation [14,21] . Four acetone molecules are present in the unit cell.…”
Section: Methodssupporting
confidence: 87%
“…Cryptophanes, are one such class of molecules, [12] contain two bowl shaped cyclic molecular systems (cyclotribenzylenes or its derivatives), joined together with three linkers. Changing linker size changes the free space of the cavity considerably [13,14] . Cryptophanes are well studied for entrapment of small neutral guest molecules CHCl 3 , CH 2 Cl 2 , CHFClBr, [13a] cationic organic molecules, [15,16] metal ions, [17] and gases like Xe, CFCs, CH 4 in solution phase [13,18] .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations